Silencing Scandal: Hector Malot's Les millions honteux. (3rd April 2022) - Johnson, Warren
ABSTRACT : Hector Malot's 1882 novel, Les millions honteux, highlights the interconnections between money and representational practice. Malot's critique in this neglected text of the construction of personal reputation through journalistic manipulation demonstrates the inextricable linkage between scandal and the press, and suggests the way that scandals themselves might be constructed or inflated like public images by unscrupulous journalists.